Factors Affecting the Adaptive Reuse Process for Historical Buildings in Kurdistan Region - An analytical study of Qubahan School as Historical Case Study - Barakat, Armang I.; Goriel, Wafaa A. (Sulaimani Journal for Engineering Sciences, 2019)
Identifying the conditions and the considerations in a selection of compatible new use for historical building in Kurdistan region in general and for Qubahan school especially considered an essential need to get a full understanding of the research problem which represented by the lack of specific studies about adaptive reuse proposal for the school. Additionally, Department of Antiquities in Duhok doesn't have the future plans for reusing this historical building. Adaptive reuse as a process after Conservation phase for any Historical building consider the main tool to retain and preserve the significance of existing heritage fabric, buildings' characters. And as known it applies to places a new use and continuing use. In this way, there is necessary to establish some basic criteria and specific guidelines for the reuse of historic buildings in Kurdistan region, especially for Qubahan School. Accordingly, this paper focuses on studying the factors that affect the reusing process of Qubahan School. Also, this paper aims to explore the possibilities of adaptive reuse of this historical school as a part of the rehabilitation process, which is managed by Department of Antiquities. To achieve this aim, this study adopted the analyzing method of Qubahan School in two levels: the first level is an Analytical survey related to the cultural, site, environmental, and architectural characteristics. at the second level comes the Space syntax analysis on functional layout of building to define the role of spatial configuration and to specify how the new use effect by space spatial characteristics. This study gives a vision about the importance of Adaptive Reuse Process as a component of the environmental development, social and economic benefits for society and individuals, basically, it is a live example of Inheritance the traditions and culture continuously for any related places.
Keywords: Adaptive Reuse; Qubahan School; Historical Buildings; spatial configuration